Colorectal invasion of endometriosis - Ozdemir, Hakan; Unal Ozdemir, Zehra; Onur Gul, Mehmet (Annals of Medical Research, 2021)
Aim: Endometriosis is a common gynecological disorder affecting women of reproductive age. The localization and stage of endometriosis determine the clinical course of the disease. In this study, colorectal invasion in endometriosis cases were evaluated retrospectively.Material and Methods: Between January 2011 and December 2019, female patients aged 18-60 that had undertaken colonoscopy examinations, appendectomies, colorectal resections and bowel shave was performed to remove mass in the intestinal wall. All results were evaluated retrospectively. After histopathological examinations, the results obtained, including findings of endometriosis were included in the study.Results: The mean age of patients was found to be 41.78±2.03. 30078 patients who had colonoscopy and rectosigmoidoscopy only two endometriosis was found(0.06%). Five out of 554 colorectal resection specimens (0.9%) and 8 out of 1516 appendectomy specimens were detected with endometriosis. Endometriosis was detected in 3 other cases with an invasive mass on the colon wall during gynecological operations and finally, in one patient holding the entire intestinal system along with the peritoneal surfaces in the abdomen. Altogether 19 cases of endometriosis were detected, 42% was invasion of the appendix tissue (most common) and the rectum being second with 21% most common localization.Conclusion: Colorectal invasion of the endometriosis is a rare clinical condition. The radiological appearance of the lumen obstruction could be confused with malignancy, cases that have not been diagnosed can visit emergency services with ileus due to lumen obstruction. In these cases surgical treatments are the best treatment option.